Respiratory Sinus Arrhythmia Acts as a Moderator of the Relationship Between Parental Marital Conflict and Adolescents’ Internalizing Problems - Khurshid, Sumaira; Peng, Yuan; Wang, Zhenhong (Frontiers in Neuroscience, 2019)
The present study examined the potential moderating role respiratory sinus arrhythmia (RSA) plays in the relationship between parental marital conflict and adolescents’ internalizing problems. To examine this issue, data were collected from 330 adolescents (13-14 years, 182 boys). The Chinese version of the Achenbach Youth Self-Report-2001 and the Chinese version of the Children’s Perception of Interparental Conflict were used to assess the adolescents’ internalizing problems and their perceptions of parental marital conflict. To obtain RSA data, electrocardiogram monitoring was performed on the adolescents at baseline and during a series of stress tasks (watching a film clip depicting marital conflict, a mental arithmetic task, and a speech task). The results indicated that baseline RSA and RSA reactivity to the film clip moderated the relationship between parental marital conflict and internalizing problems in early adolescents. The moderating effect of baseline RSA supported the BSCT hypothesis. Specifically, adolescents with low baseline RSA have both the highest and lowest levels of internalizing problems, depending on the level of marital conflict. In contrast, adolescents with high levels of baseline RSA have moderate levels in internalizing problems, regardless of the level of marital conflict they experience. Similarly, high marital conflict was related to internalizing problems for adolescents with less RSA suppression or RSA augmentation but not for those with greater RSA suppression. This effect was specific to stress related to marital conflict, as RSA reactivity to the mental arithmetic task and speech task did not moderate the relationship between marital conflict and internalizing problems. These findings suggest that certain profile of parasympathetic nervous activity is a risk factor for internalizing problems particularly for those who experience high-conflict environments.